The complexity of satellite deoxyribonucleic acid in a higher plant. - Sinclair, J (1975)
Purified satellite DNA from melon (Cucumis melo) was shown to contain at least two components from thermal-denaturation and renaturation studies. Two components were separated after partial renaturation, a fast-renaturing fraction similar in complexity to mouse satellite DNA, and one with 6000 times greater complexity. Both components renatured very accurately, indicating a minimum of sequence divergence. Centrifugation of the purified satellite DNA in Ag+/Cs2SO4 gradients resolved two major and several minor fractions. The two major fractions were only slightly enriched for fast- or slow-renaturing sequences.